2020
DOI: 10.38043/jmb.v17i2.2355
|View full text |Cite
|
Sign up to set email alerts
|

Implikasi Profitabilitas Terhadap Nilai Perusahaan dan Kebijakan Dividen Sebagai Variabel Intervening (Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia Periode 2009-2016)

Abstract: This research examines and discovers the implication of profitability on firm value, and dividend policy as mediating effect at mining companies which are listed on Indonesian Stock Exchange in 2009-2016 with total samples, 5 companies. This study using path analysis to solve the problem with the help of SPSS 24. The result shows that Profitability and dividend policy have positive effect and significant on firm value, Profitability has negative effect on dividend policy, and dividend policy has no mediating e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
9

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 6 publications
0
2
0
9
Order By: Relevance
“…Research conducted by Berezinets et al, (2017), andMartha et al, (2018), showed that dividend policy has a negative and insignificant effect on the value of the company, while research Effendy, (2020), Husna &Rahayu, (2020), andLubis et al, (2017), stated that dividend policy has a positive and insignificant effect on the company's value. In contrast to the research results of Nurvianda et al, (2019), Ahmad et al, (2018), Hairudin et al, (2020), andKeintjem et al, (2020) stated that dividend policy has a positive and significant effect on the company's value.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Research conducted by Berezinets et al, (2017), andMartha et al, (2018), showed that dividend policy has a negative and insignificant effect on the value of the company, while research Effendy, (2020), Husna &Rahayu, (2020), andLubis et al, (2017), stated that dividend policy has a positive and insignificant effect on the company's value. In contrast to the research results of Nurvianda et al, (2019), Ahmad et al, (2018), Hairudin et al, (2020), andKeintjem et al, (2020) stated that dividend policy has a positive and significant effect on the company's value.…”
Section: Introductionmentioning
confidence: 72%
“…Furthermore, for profitability to the value of the company, Martha et al, 2018), Husna & Rahayu, (2020), Hairudin et al, (2020), Hikma Niar, H. Abdul Rahman Mus, Hj. Masdar Mas'ud, (2018), and Lubis et al, (2017 stated that profitability has a positive effect on the company's value, in contrast to the research results of Keintjem et al, (2020) profitability has no significant effect on the company's value.…”
Section: Introductionmentioning
confidence: 99%
“…Hasil penelitian Husna dan Rahayu (2020) menunjukkan pertumbuhan perusahaan dan profitabilitas memiliki pengaruh pada nilai perusahaan, dan kebijakan dividen tidak berpengaruh pada nilai perusahaan. Penelitian Hairudin et al (2020) memberikan hasil profitabilitas tidak berpengaruh pada kebijakan dividen. Profitabilitas dan kebijakan dividen berpengaruh positif signifikan pada nilai perusahaan, dan kebijakan dividen tidak mampu mempengaruhi profitabilitas terhadap nilai perusahaan.…”
Section: Kajian Riset Sebelumnyaunclassified
“…Penelitian ini tidak sejalan dengan penelitian yang telah dilakukan oleh (Fitriana, 2014), (Setyowati et al, 2018), (Ikbal et al, 2011), (Sari, 2015), dan (Anggraeni & Sulhan, 2020) dimana profitabilitas memiliki pengaruh positif terhadap kebijakan dividen. Namun penelitian ini sejalan dengan (Maladjian & Khoury, 2014), dan (Hairudin et al, 2020) yang menyatakan bahwa profitabilitas berpengaruh negatif terhadap kebijakan dividen.…”
Section: Pengaruh Profitabilitas Terhadap Kebijakan Dividenunclassified